FAKTOR – FAKTOR YANG MEMPENGARUHI NIAT BERWIRAUSAHA MAHASISWA - Kukuh Mulyanto (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2017)
Socio-economic issues such as poverty, unemployment productive ageare a major challenge for Indonesia when entering the free market andglobal competition. As one of the leading Human Resources, college needs toknow the factors that influence students in entrepreneurship. Various factorsthat influence entrepreneurial intentions in students, especially the attitudeand contextual factors. Population is Economic Education Student in STIETotalwin Semarang. Data were analyzed using multiple linear regression.The results of this study indicate that the attitude positive effect onentrepreneurial intention of students, while the contextual factors positivelyaffects student entrepreneurial intention.